ANALYSIS OF STUDENTS’ STEM LITERACY BASED ON GENDER DIFFERENCES IN SCIENCE LEARNING - Annisa Nurramadhani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
STEM literacy can be defined as an ability to identify, apply, and to integrate the concept of science, technology, engineering, and mathematics to innovate and solve the complex problem. Especially in science learning that approached by the strategies like STEM. Because this revolution industry 4.0 era, students are demand to workface in integrate to their living life. So, they are asked can solved the problem properly, giving the solution for global problem wisely. In the process of learning science with project, somehow students show their own performance. The results of project-based learning pointing the different result of performing based on gender differences. The method that is used is descriptive. The subject in this research is the student’s preservice teacher of science and biology education study program for about 21 students with 4 boys and 17 girls in the second semester of the freshmen. The research is conducted in basic physic laboratory. The laboratory activity is using STEM approach with project. The students are divided into 4 groups and each group consist of boy’s students. The research instrument to take the data that is used are observation sheet for student’s performance in laboratory activity and questionnaire of students for their laboratory activity per-aspect that describes their competences in science, technology, engineering, and mathematics. The technique to take the data that is used in this research are video recording, observation, and informal interview. The results are student’s STEM literacy has different score based on the gender differences. In the first project, sailor boat, boys reach the higher percentages in aspect science, engineering, and technology, while girls reach the higher percentages in science and technology. The second project, let’s fun with music, boys reach the higher percentages in aspect science, engineering, and technology, while girls reach the higher percentages in science and engineering. In both of project, boys and girls reach the lowest percentages in mathematics aspect. But, in whole score boys has reached higher than girls.  It can be concluded that boys are outperformed than girls in STEM literacy in science learning especially in basic physics laboratory activity.